Mycoflora and absence of aflatoxin contamination of commercialized cassava chips in Benin, West Africa - Gnonlonfin, G.J.B.; Adjovi, Y.C.S.; Katerere, D.R.; Shephard, G.S.; Sanni, A.; Brimer, L. (Elsevier, 2012)
Studies conducted in Benin, in which the main staple foods are maize, cassava, groundnuts and yams, showed high levels of aflatoxin residues in blood of the exposed population. The natural contamination with fungi and aflatoxins in cassava chips sold at markets in Benin, West Africa was investigated. A total of sixty samples were sampled from open markets in 11 districts of 3 agroecological zones and analyzed for the presence of mycoflora and aflatoxin B1, B2, G1 and G2. Fourteen genera of fungi were associated with marketed dried cassava chips. Within these, twenty- two isolates were identified to species level, whereas four were identified only to genus. The dominating fungal species isolated were Rhizopus oryzae, Nigrospora oryzae, Chrysonilia sitophila, Cladosporium resinae, Cladosporium herbarum, Apergillus niger and Aspergillus flavus. Fifty-four out of sixty samples were contaminated with A. flavus. The rate of occurrence in CFU/g of A. flavus fungi was lower than for all other fungal species together. Aflatoxin was not detected in any of the samples analyzed using HPLC with post-column photochemical derivatization and fluorescence detection. The limit of detection (LOD) was 0.1 ?g/kg. Results from this study suggest cassava chips are unlikely to be a source of aflatoxin in Benin, and that other staples such as maize and groundnuts are more important in aflatoxin exposure. Therefore it can be speculated that staples like maize and groundnut are more important in aflatoxin exposure.